Application Of Fuzzy Logic In Determining Full Cream Milk Drink RecommendationsBased On Milk Price And Nutrition - Jasmine Maulida luthfiana; Fiqri Nurfadillah; Ester Angeline; Nanda Octavia; Muhammad Danang Mukti Darmawan; Makayla Fayly W; Firli Aflahatul; Muh. Kholid Irhamni Maulana; Novia Annisa Aqsha; Muhammad Razev Azmi Zaini; Nurhasanah; Dinda Marina; Ersa Athiyyah; Puspa Ayu Setyaningrum; Muh. Daffa Akbar Putra Palsan; Diana Yati; Mrr. Lukie Trianawati (Batrisya Education, 2025)
Fuzzy logic is part of the branch of mathematics that analyzes random number processes using computer science-based mathematical statistical theory. This research aims to use the fuzzy method to determine the recommended full-cream milk drink based on the price and nutrition of the packaged milk itself using fuzzy logic, observation, and literature study. The fuzzy method used is the Mamdani method with the assistance of the Fuzzy Inference System (FIS) in MATLAB R2015a application. Based on the research results, it is found that sample milks 4, 5, and 6 are suitable for recommendation to consumers because, through fuzzy logic analysis, they obtained membership degree values of 0.92, 0.92, and 0.91 respectively, which fall into the category of highly recommended.